Translation Procedures of The Animated Movie “A Stork’s Journey” - Wedriyani, Kadek Ira; Hikmaharyanti , Putu Desi Anggerina (STKIP AGAMA HINDU SINGARAJA, 2024)
This study focuses on examining the types of translation procedures in the Indonesian rendition of the animated film